qanda-logo
search-icon
Símbolos
apple-logo
google-play-logo
Problema
solution-image
(a) $f\left(x\right)=6x^{3}+2x^{2}-x-2$ $f\left(x\right)=cos\left(ln\left(3+x^{2}\right)\right)+\left(2x^{4}-1\right)^{3}$ (b) a (e) $f\left(x\right)=\dfrac {3x^{2}+4} {x^{2-5x+3}}$ (d) f(x) = 2 arctan - cos (6arctan ) (e) f (r) = sen $rcosx-tanx+scx$ (0 $f\left(x\right)=\left(2x^{3}+4r\right)\left(6x^{3}-x^{2}+4x+5\right)$ (g) $f\left(x\right)=sn^{2}\left(x^{2}-1$ (h) $f\left(x\right)=son^{2}\left(\dfrac {x+1} {x^{2}+2}\right)$ (1) $f\left(x\right)=\sqrt{x^{2}+\sqrt{x^{3}+} 2} $ G) $f\left(x\right)=cs^{2}\left(\sqrt{x^{2}+1} \right)$ (k) $f\left(x\right)=an^{2}\left(\sqrt{x^{2}+3} \right)cos^{2}\left(\sqrt{x^{2}+3} \right)$ (1) $f\left(x\right)=xc^{x}+x^{3}\left(c^{x^{2}}+2c^{2}\right)$ (m) $f\left(x\right)=lm\left(x^{2}+2\right)$ (n) $f\left(x\right)=ln\left(x+1\right)scn\left(5x^{2}+3\right)$ (o) $f\left(x\right)=\dfrac {ln\left(x+c^{2}\right)} {x+2snx}$ (p) $f\left(x\right)=\dfrac {-c^{-1}} {c^{x+c^{-}}}$ (9) $f\left(x\right)=ln\dfrac {\sqrt{x^{3}+scn} x+c^{ta}} {xscnx+c=}$ (t) $f\left(x\right)=x^{2}+c^{-}$ lan (s) $y=x^{4}\left(1-2x^{3}\right)^{2}$ (t) $y=tan^{2}\left(oocx^{3}\right)$
Bachillerato
Cálculo
Búsquedas: 179
Contenido de la pregunta
me toca derivar ayuda por favor
Solución
answer-user-profile-image
Profesor de Qanda - Luis_Alber
answer-reply-image
answer-reply-image